Efektivitas Pemberian Pakan Ikan Red Devil (Amphilophus sp.) sebagai Pakan Alternatif terhadap Pertumbuhan Morfometrik dan Bobot Badan Ikan Patin (Pangasius sp.) - Muhammad Reza Batubara; Efrida Pima Sari Tambunan (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to determine the effectiveness of Red Devil fish (Amphilophus sp.) as an alternative feed on the morphometric growth and body weight of catfish (Pangasius sp.). The method used was a completely randomized design (CRD) consisting of five feed treatments, each replicated four times, resulting in 20 experimental units. The treatments included: (a) P0: 100% commercial feed, (b) P1: 100% Red Devil feed, (c) P2: 75% commercial feed + 25% Red Devil feed, (d) P3: 50% commercial feed + 50% Red Devil feed, and (e) P4: 25% commercial feed + 75% Red Devil feed. Data were analyzed using ANOVA followed by Duncan’s test at a 5% significance level. The results showed that all five treatments significantly affected the morphometric growth and body weight of catfish. The highest performance was obtained in P1 (100% Red Devil feed), which produced a head length of 2.72 cm, tail length of 1.70 cm, total length of 10.25 cm, and an absolute length growth of 3.12 cm. The body weight reached 9.49 g with a specific growth rate (SGR) of 0.180.   Keywords: Alternative, Feed, Morphometric, Pangasius, Red Devil